PERAN KELUARGA DALAM MENUMBUHKAN PERILAKU POSITIF ANAK MELALUI PENDEKATAN BEHAVIOR - Jawandi, Ahmad; Adi Putro, Eko (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2019)
Family becomes the smallest social unit in a society. The socialization process was first carried outin the family. Educate children to get to know children and how to treat children according to theirneeds and development. By recognizing and understanding their children, parents as educators inthe family will be able to increase their potential as optimally as possible, especially in formingpositive behaviors. Behavior is any form of action taken or planned. While positive behavior is anaction that is in accordance with the character, culture, norms and noble values in the community.In order for children to grow and develop optimally, the family or parents need to increase theirrole. Along with the times and the assimilation of culture in the era of globalization of positivebehavior in children such as manners, tolerance, caring for others and respect for others isincreasingly lost. The effort that can be taken to develop positive behavior of children in the familyenvironment is through a behavioral approach.The target of service is the Beneficiary Family(KPM) of the Hope Family Program in Wonosegoro District. The purpose of this communityservice activity is to provide training methods in enhancing family roles to foster positive behaviorthrough a behavioral approach. The method used in this community service is the behaviorismapproach in increasing family roles to form positive behavior. In this behavior approach usesseveral techniques, namely modeling techniques, reinforcement techniques and Asertive trainingtechniques. The implementation of community service carried out with seminars and trainingthrough lectures, discussions and brainstorming, questions and answers, and direct practice. Theimplementation of the behavioral approach training as an effort to improve the family's role informing positive behavior was Carried out in four meetings. The expected result of communityservice is the realization of parents' understanding of the importance of the role of the family infostering positive behaviors of children that are applied in daily life through a behavioral approach.Keywords: Family Role, Positive Behavior, Behavior Approach